Alur Kegiatan Empty Container dalam Kelancaran Ekspor dan Impor di Depo PT. Citra Prima Container Surabaya - Wahyu Mas Izudin, Ahmad; Akhmad, Ekka Pujo Ariesanto (Universitas Hang Tuah, 2021)
A container depot is a place for storing empty containers or containers, a place for cleaning, repairing containers and a place for conducting container surveys when containers enter or leave. The purpose of this study was to determine the flow of empty container activities in the smooth export and import at the depot of PT. Citra Prima Container Surabaya. The method used to determine the flow of empty container activities in the smooth export and import at the depot of PT. Citra Prima Container Surabaya is a qualitative method, namely interviews with the Depo Container workers, observation, and documentation. The research results obtained, namely, the importance of cooperation and coordination between the field and the office. When there is a traffic jam on Kalmar's equipment in the container block which is usually for stacking at the depot and unloading, then coordination needs to be optimized between foreman, crane, and security to reduce congestion. The importance of classifying Grade Container with the aim of simplifying the work of employees.